Carbonic anhydrase versatility: from pH regulation to CO2 sensing and metabolism - Supuran, Claudiu T. (Frontiers in Molecular Biosciences, 2023)
Seen for decades primarily as involved only in pH regulation, the carbonic anhydrase (CA, EC 4.2.1.1) superfamily of enzymes are more than that. CO2, bicarbonate and protons, the CA physiological substrates, are indeed the main buffering system in organisms belonging to all life kingdoms, but in the last period the involvement of the eight genetically distinct CA families in chemical sensing, metabolism and several other crucial physiologic processes has seen a relevant progress. Interference with CA activity, both by inhibiting and activating these enzymes, has thus led to novel application for CA inhibitors and activators in innovative biomedical and environmental fields. In this perspective article I will discuss recent advances which allowed a deeper understanding of the biochemistry of these versatile enzymes and various application of their modulators of activity.